The Influence of Innovation on Increasing Sales of MSME Products - Andi Tenri Ampa (International Journal of Integrative Sciences, 2023)
This research aims to determine the effect of product innovation on increasing product sales for Micro, Small and Medium Enterprises. This research uses quantitative research, the method for collecting data used is by filling out a questionnaire using a distributed Google form. The population in this study were students who had businesses and the sample was 40 respondents taken from students who were micro, small and medium businesses. The data analysis technique used is multiple linear regression analysis. Based on the research results, it shows that testing was carried out on students as Micro, Small and Medium Enterprises actors simultaneously, three variables (X) had a significant influence together on increasing sales of Micro, Small and Medium Enterprises products (Y). Based on the results of the partial significance test, the Innovation variable (X1) has a positive and significant influence on increasing product sales for Micro, Small and Medium Enterprises (Y)